Reverse end-to-side technique (RETS) – supercharge and babysitting effect in median and ulnar nerve injuries. Case studies and surgical technique - Piotr Czarnecki; Michał Górecki (Chirurgia Narządów Ruchu i Ortopedia Polska, 2023)
High nerve damage at the shoulder or elbow is associated with a long regeneration period for effectors-muscles located within the hand, leading to their irreversible atrophy and permanent dysfunction. Advanced microsurgical reconstructive techniques, such as end-to-side (ETS) sutures, reverse end-to-side (RETS) reconstruction (so-called supercharge/babysitting procedure), or nerve transfers within the hand, shorten the interval and thus the recovery time or provide continuous stimulation of the effector before the regeneration of the native axons of the nerve. The paper aims to present the authors’ results after treatment of a high injury of the ulnar and median nerves with additional RETS performed based on the results of three clinical cases. Two patients No 1 and 2 had a high ulnar nerve injury at the elbow level due to a distal humerus fracture. Nerve neurolysis was performed at the level of the primary lesion, followed by a reverse end-to-side transfer of the anterior interosseous nerve to the deep motor branch of the ulnar nerve. The patient No 3 with damage to the median nerve due to a fracture of the shaft of the radius. Neurolysis of the preserved part of the nerve, resection of the neuroma, and direct suture of the damaged part of the nerve were performed, as well as a simultaneous RETS transfer of the anterior interosseous nerve to the thenar motor branch of the median nerve. All presented patients had significant signs of improvement, with full to partial motor recovery of the nerves supported by supercharge/babysitting RETS technique. It is valuable, especially in borderline cases when the decision is between neurolysis/repair alone or nerve transfer is difficult to take and not clearly defined.